(untitled) (Experimental biology, 2016)
It was revealed that in total RNA preparations isolated from wheat germ continuously detects small cytoplasmic RNA (scRNA) of about 55 nucleotides corresponding to the 5’-terminal fragment of 5.3S RNA, which in turn, is a fragment of 18S rRNA. This cytoplasmic RNA was detected in plant cells belonging to different taxa, as well as in rat liver cells, so that the investigated process of discrete 18S rRNA fragmentation should be sufficiently universal phenomenon. It was established that the content of investigated 18S rRNA fragment is much lower in young plant shoots rather than in dry and germinating seeds, and that its content increases if germinated seeds were exposed to heat shock (37° C). The process of discrete fragmentation of 18S rRNA probably could be the regulatory mechanism started in response to environmental stress.